Inside Cover: Binding Mode and Structure–Activity Relationships around Direct Inhibitors of the Nrf2–Keap1 Complex (ChemMedChem 4/2014). Issue 4 (April 2014) - Jnoff, Eric; Albrecht, Claudia; Barker, John J.; Barker, Oliver; Beaumont, Edward; Bromidge, Steven; Brookfield, Frederick; Brooks, Mark; Bubert, Christian; Ceska, Tom; Corden, Vincent; Dawson, Graham; et al.
<x xml:space="preserve">Abstract</x> The inside cover picture shows the activation of the Nrf2 pathway induced by a small molecule (NCE) disrupting the Keap1–Nrf2 interaction in a noncovalent manner. Crystallographic elucidation of its binding mode helped to focus and drive the drug design process more effectively and efficiently. For further details, see the Communication by Eric Jnoff et al. on p. 699 ff. Artwork by Réjane Leporcq.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>